Optimalisasi Proses Pendaftaran Produk UMKM ke Ritel: Studi Kasus pada Usaha Stik Talas - Setiawan, Aris; Rizki Fakhrul Yahya; Jaurino; Wilda Sari (Indra Institute Research & Publication, 2024)
This service aims to help Stik Talas MSMEs to register products in retail businesses. This service begins with the observation process, administrative management, dissemination and preparation of service activity reports. The service team educates partners about the importance of improving the quality and quantity of their products. In this activity, education is also given on the importance of expanding the market to sell their products. Furthermore, the service team helped Stik Talas MSMEs to fill in the forms on the digital application that must be fulfilled by business owners if they want to market their products in retail businesses. All documents that must be inputted into the system have been carried out jointly between the service team and partners. The success of this activity is expected to spur all MSMEs to continue to increase the marketing expansion of their products so that it will have an impact on increasing the sales volume of business products.